Utilizing Game Based Learning to Facilitating Students’ Vocabulary Through Baamboozle (Lembaga Pengembangan Kinerja Dosen, 2026)
This study explores the use of Game-Based Learning (GBL) through Baamboozle to facilitate vocabulary acquisition among junior high school students. Recognizing that vocabulary mastery is essential for effective English communication, this research addresses the challenge of students' low motivation and limited vocabulary knowledge. The study employed a qualitative case study method, involving 20 seventh-grade students from a junior high school in Karawang, Indonesia. Data were collected through observations, interviews, and open-ended questionnaires. The findings indicate that the implementation of Baamboozle created a more engaging, interactive, and enjoyable learning environment. Students demonstrated increased motivation, active participation, collaborative learning, and improved vocabulary retention. Despite encountering technical constraints, such as limited access to devices and unstable internet connections, students reported positive experiences and preferred game-based learning to traditional methods. The study concludes that Baamboozle is an effective educational tool for vocabulary learning, promoting student-centered, collaborative, and motivating language instruction.